2020
DOI: 10.1161/circresaha.120.317703
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Can Associate With SARS-CoV-2 RNA and Are Hyperactivated in COVID-19

Abstract: Rationale: In addition to the overwhelming lung inflammation that prevails in COVID-19, hypercoagulation and thrombosis contribute to the lethality of subjects infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Platelets are chiefly implicated in thrombosis. Moreover, they can interact with viruses and are an important source of inflammatory mediators. While a lower platelet count is associated with severity and mortality, little is known about platelet function during COVI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
617
5
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(695 citation statements)
references
References 86 publications
39
617
5
5
Order By: Relevance
“…Our findings confirm the suggested relevance of PLT-EVs in Sars-CoV-2 infection as recently shown by Zaid et al [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings confirm the suggested relevance of PLT-EVs in Sars-CoV-2 infection as recently shown by Zaid et al [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…In their work, Zaid et al [ 22 ] characterized PLT-EVs starting from manipulated blood, i.e., platelet rich plasma (PRP), after 1000 g centrifugation, in which PLT were subsequently removed to obtain plasma-free-platelet (PFP). PLT-EVs were then identified by FC on forward scatter (FSC) parameter, by using silica beads as a reference to assess their dimension.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma levels of α-granule proteins PF4 and soluble CD40L were higher in COVID-19 patients, further indicating activated platelets in vivo ( Figure 1B). While earlier studies also reported enhanced α granule release 9,10 , our study adds to this that dense granules likely are not affected in COVID-19 patients not requiring intensive care.…”
Section: Accepted Manuscriptmentioning
confidence: 38%
“…In this context, circulating SARS-CoV-2 RNA (RNAemia) has been highlighted as a promising prognostic biomarker in hospitalized COVID-19 patients, as it is associated with disease severity 7 and mortality [8][9][10] , with an estimated prevalence of 10% (95% CI 5-18%, random effects model) 7 . Further, we hypothesized that the acute and profound alterations in the innate and adaptive immune system in COVID-19 patients 3,[11][12][13] , especially in RNAemic patients [14][15][16][17][18] , will be accompanied by marked changes in the circulating proteome and interactome and that the proteome in COVID-19 patients will highlight mechanistically relevant signatures and trajectories, when compared to non-COVID-19 sepsis and healthy controls. Thus far, proteomics studies have focused on the determination of protein biomarkers of COVID-19 severity [19][20][21][22] , but have not assessed the longitudinal relationship between proteomic changes, RNAemia and 28-day mortality.…”
Section: Introductionmentioning
confidence: 99%